2022
DOI: 10.1136/archdischild-2022-324455
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of reported postacute health outcomes in children with SARS-CoV-2 infection: a systematic review

Abstract: ObjectiveTo systematically assess the robustness of reported postacute SARS-CoV-2 infection health outcomes in children.MethodsA search on PubMed and Web of Science was conducted to identify studies published up to 22 January 2022 that reported on postacute SARS-CoV-2 infection health outcomes in children (<18 years) with follow-up of ≥2 months since detection of infection or ≥1 month since recovery from acute illness. We assessed the consideration of confounding bias and causality, as well as the risk of b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“… 38 Fourth, we have not captured information on potential long-term consequences of COVID-19, although claims for frequent pediatric post–COVID-19 condition may be unfounded. 39 Fifth, children and adolescents in the studied population were mostly unvaccinated, and our analyses were underpowered to address the impact of vaccination. However, outcomes were already excellent for pediatric infections and even more so for reinfections.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Fourth, we have not captured information on potential long-term consequences of COVID-19, although claims for frequent pediatric post–COVID-19 condition may be unfounded. 39 Fifth, children and adolescents in the studied population were mostly unvaccinated, and our analyses were underpowered to address the impact of vaccination. However, outcomes were already excellent for pediatric infections and even more so for reinfections.…”
Section: Discussionmentioning
confidence: 99%
“…These authors did not stratify analyses by study design and pointed out the considerable risk of bias in particular because of the lack of standardised definitions of symptoms and a high level of heterogeneity [ 16 ]. Two recent systematic reviews including studies up to early 2022 reported rates of post-COVID syndrome in children ranging from 0% to 70% [ 52 , 53 ]. One of these reviews highlighted the critical risk of bias across studies, mostly due to confounding [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews including studies up to early 2022 reported rates of post-COVID syndrome in children ranging from 0% to 70% [ 52 , 53 ]. One of these reviews highlighted the critical risk of bias across studies, mostly due to confounding [ 52 ]. Regarding healthcare resources use, Magnusson et al conducted a before and after study to explore if the use of healthcare services is mildly increased among children and adolescents after COVID-19, mostly in primary care settings due to respiratory and general unspecified conditions during the first months, with limited impact on healthcare services, especially in children under 5 years of age [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we have not captured information on potential long-term consequences of COVID-19 infection in children and adolescents, although claims for frequent pediatric long-COVID-19 may be unfounded. 30 Fourth, children and adolescents in the studied population were mostly unvaccinated and our analyses were underpowered to address the impact of vaccination. However, outcomes were already excellent for pediatric COVID-19 infections and even more so for reinfections.…”
Section: Discussionmentioning
confidence: 99%